2014
DOI: 10.1002/2013pa002466
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature variations in the western Mediterranean Sea over the last 20 kyr: A dual‐organic proxy (U K′ 37 and LDI) approach

Abstract: A high-resolution sea surface temperature (SST) reconstruction of the western Mediterranean was accomplished using two independent, algae-based molecular organic proxies, i.e., the U K′ 37 index based on long-chain unsaturated ketones and the novel long-chain diol index (LDI) based on the relative abundances of C 28 and C 30 1,13-and 1,15-diols. Two marine records, from the western and eastern Alboran Sea basin, spanning the last 14 and 20 kyr, respectively, were studied. Results from the surface sediments sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 104 publications
(169 reference statements)
3
54
0
2
Order By: Relevance
“…However, both the U k 0 37 and TEX 86 proxies have their limitations. Nevertheless, the reconstruction of past SST using the LDI has been successful in various marine environments, predominantly in temperate regions (Jonas et al, 2017;Naafs et al, 2012;Plancq et al, 2015;Rampen et al, 2012;Rodrigo-Gámiz et al, 2014;Smith et al, 2013). Furthermore, studies comparing Recently, a new SST proxy, the long-chain diol index (LDI), was developed based on the distribution of longchain diols (LCDs; Rampen et al, 2012), that is, the ratio of the C 30 1,15-diol over the sum of C 28 1,13; C 30 1,13; and C 30 1,15-diols, with higher fractional abundances of 1,15-diol observed at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both the U k 0 37 and TEX 86 proxies have their limitations. Nevertheless, the reconstruction of past SST using the LDI has been successful in various marine environments, predominantly in temperate regions (Jonas et al, 2017;Naafs et al, 2012;Plancq et al, 2015;Rampen et al, 2012;Rodrigo-Gámiz et al, 2014;Smith et al, 2013). Furthermore, studies comparing Recently, a new SST proxy, the long-chain diol index (LDI), was developed based on the distribution of longchain diols (LCDs; Rampen et al, 2012), that is, the ratio of the C 30 1,15-diol over the sum of C 28 1,13; C 30 1,13; and C 30 1,15-diols, with higher fractional abundances of 1,15-diol observed at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The LDI seems to be independent from salinity but is impacted by freshwater input (De Bar et al, 2016;Lattaud, Kim, et al, 2017) and oxic degradation (Rodrigo-Gámiz et al, 2016). Nevertheless, the reconstruction of past SST using the LDI has been successful in various marine environments, predominantly in temperate regions (Jonas et al, 2017;Naafs et al, 2012;Plancq et al, 2015;Rampen et al, 2012;Rodrigo-Gámiz et al, 2014;Smith et al, 2013). However, the LDI has, up to now, never been applied in subpolar regions.…”
Section: Introductionmentioning
confidence: 99%
“…7.5 and 8.0 °C, for the U K´3 7 and TEX H 86, respectively. Interestingly, other LDI and U K´3 7 applications on 20 glacial-interglacial timescales also show somewhat greater amplitudes for the LDI records as compared to the U K´3 7, (Rampen et al, 2012;Lopes dos Santos et al, 2013;Rodrigo-Gámiz et al, 2014;Jonas et al, 2017). This might potentially suggest that the surface sediment calibration of the LDI requires some modification, e.g., a lower slope.…”
Section: Sea Surface Temperature Evolutionmentioning
confidence: 99%
“…Preliminary applications in sediment cores of these LCD proxies have shown that the LDI, as well as the Diol Index, are promising as paleotemperature and past upwelling proxies (e.g., Pancost et al, 2009;Lopes dos Santos et al, 2012;Rampen et al, 2012;Seki et al, 2012;Rodrigo-Gámiz et al, 2014;Plancq et al, 2015;Jonas et al, 2017). However, a number of uncertainties still exist in the application of these biomarkers.…”
mentioning
confidence: 99%
“…For instance, in the westernmost Mediterranean Sea, major periodicities at 1300 yr and 1515 yr, linked with North Atlantic climate variability and the African monsoon system were found out along the past 20,000 yr. Other major periodicities of 2000 yr and 5000 yr are related to solar activity. Minor secondary millennial to centennial cycles stretching along 650 yr, 1087 yr, and 3000 yr are still unknown [13]. In this work, the aim was studying the Holocene cyclostratigraphy along a core from an endorheic system (sebkha Sidi Mansour) located at the coast of the Mediterranean Sea.…”
Section: Introduction Sun Activity and Its Effect On Climatic Cyclicitymentioning
confidence: 99%